2020
DOI: 10.1177/0084672420931204
|View full text |Cite
|
Sign up to set email alerts
|

On being moderate and peaceful: Why Islamic political moderateness promotes outgroup tolerance and reconciliation

Abstract: Islamic moderateness is said to be one of the key factors that contribute to the promotion of peace in Muslim societies. We present an empirical study conducted in Indonesia ( N = 299) that assessed Islamic political moderateness and examined its role in explaining Muslims’ tolerance towards non-Muslims, as well as the first group’s support for making reconciliation with the latter group. We found as hypothesised that Islamic political moderateness was a positive predictor of outgroup tolerance, because of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 81 publications
(103 reference statements)
0
11
0
2
Order By: Relevance
“…Melalui pemanfaatan teknologi dalam desain platform media sosial, proses internalisasi konten juga dipertimbangkan, sebagaimana adanya daya dukung atau karisma dari para ustadz yang memberikan ceramah online (Qudsy, 2018). Hal ini menuntut para pengguna untuk selektif dalam mencari konten keagamaan (Gumilar et al, 2017;Nuryana, 2019;Sari, 2017;Zaduqisti et al, 2020). Internalisasi konten positif juga ditingkatkan melalui penyebaran akun dan platform media sosial sehingga menghasilkan kebermanfaatan positif bagi masyarakat (Faiqah et al, 2018).…”
Section: Pembahasanunclassified
“…Melalui pemanfaatan teknologi dalam desain platform media sosial, proses internalisasi konten juga dipertimbangkan, sebagaimana adanya daya dukung atau karisma dari para ustadz yang memberikan ceramah online (Qudsy, 2018). Hal ini menuntut para pengguna untuk selektif dalam mencari konten keagamaan (Gumilar et al, 2017;Nuryana, 2019;Sari, 2017;Zaduqisti et al, 2020). Internalisasi konten positif juga ditingkatkan melalui penyebaran akun dan platform media sosial sehingga menghasilkan kebermanfaatan positif bagi masyarakat (Faiqah et al, 2018).…”
Section: Pembahasanunclassified
“…On the other contrary, Sufis' tolerance towards different religious groups, thoughts, schools and communities can overcome psychological barriers for Sufi order in social interaction. Tolerance including towards non-Muslims can overcome socio-psychological barriers and facilitate reconciliation with different groups (Zaduqisti et al 2020). A study conducted by Zaduqisti et al shows that a moderate attitude can pave the way for Muslims to have a positive attitude towards peace and reconciliation with non-Muslims.…”
Section: From 'Tanbih' and 'Mahabbah' To Knit Tolerancementioning
confidence: 99%
“…Even the benefit of the out-group's expressions of empathy and responsibility in facilitating a process of reconciliation may backfire when in-group members distrust the out-group (Nadler & Liviatan, 2006). Supporting these rationales, research by Zaduqisti et al (2020), for example, found that the less Muslims endorsed a moderate version of Islam they demonstrated more distrust toward non-Muslims. The second reason relates to the chronic tendency of radicals to engage in out-group blame, which reflects moral disengagement (Bandura, 2004).…”
Section: Radicalism and Its Negative Consequencesmentioning
confidence: 99%